Volunteer tourism : the lifestyle politics of international development - Butcher, Jim (Contemporary geographies of leisure, tourism and mobility, 2015)
"Just a generation ago the notion that holidays should be invested with ethical and political significance would have sounded odd. Today it is part of the lifestyle political landscape. Volunteer tourism is indicative of the growth of lifestyle strategies intended to exhibit care and responsibility towards others less fortunate, strategies aligned closely with developing one's ethical identity and sense of global responsibility. Today it sits alongside telethons, pay-per-click, Fair Trade and ethical consumption generally as a way to "make a difference". In recent years a number of books and papers have been published on this issue. However these accounts fail to address a key issue: what does the growth of volunteer tourism tell us about the way development is understood and acted upon in contemporary society? Also, what do changes in volunteering in the post 1945 period show us about contemporary social consciousness? This book aims to develop a rounded understanding of the phenomenon by contextualising these issues within a wider historical and sociological framework, including the changes in what is regarded as 'political'. It focuses on the significant changes in political consciousness in the post-war period from the Peace Corps and VSO based on people's skills, through to today where there are a host of voluntourism oriented companies offering ubiquitous opportunities for wide range of people, premised upon their aspiration to adopt an ethical lifestyle. This thought provoking volume drawing on development, political and sociological theory is essential reading for students, researchers and academics interested in the phenomenon of volunteer tourism and its development"--